Harbour seal (Phoca vitulina) abundance within the Firth of Tay and Eden Estuary, Scotland:recent trends and extrapolation to extinction - Hanson, Nora; Thompson, Dave; Duck, Callan; Baxter, John; Lonergan, Mike (Aquatic Conservation: Marine and Freshwater Ecosystems, 2017)
Aerial surveys have detected alarming declines in counts of harbour seals in several regions across Scotland. Demographic data and simple models were used to examine the recent decline in the numbers of harbour seals counted in one population within a Special Area of Conservation (SAC) on the east coast of Scotland. The models suggest that the continuation of current trends would result in the species effectively disappearing from this area within the next 20 years. While the cause of the decline is unknown, it must be reducing adult survival because the high rate of decline cannot be wholly accounted for by changes in other demographic parameters. Recovery of the population to the abundance recorded at the time the SAC was designated (2005) is likely to take at least 40 years, even if the cause of the decline is immediately identified and removed. The models suggest that partial removal of the cause can have only limited benefits to population recovery, and there are unlikely to be any long-term benefits from introducing or reintroducing additional individuals while the underlying problem persists. Therefore, if the population of harbour seals in this area is to recover it is essential that the sources of the increased mortality are identified and measures are put in place to manage these.